What is the impact of child abuse on gray matter abnormalities in individuals with major depressive disorder: a case control study. Issue 1 (December 2016) - Ahn, Sung; Kyeong, Sunghyon; Suh, Sang; Kim, Jae-Jin; Chung, Tae-Sub; Seok, Jeong-Ho
Abstract Background Patients with major depressive disorder (MDD) present heterogeneous clinical symptoms, and childhood abuse is associated with deepening of psychopathology. The aim of this study was to identify structural brain abnormalities in MDD and to assess further differences in gray matter density (GMD) associated with childhood abuse in MDD. Methods Differences in regional GMD between 34 MDD patients and 26 healthy controls were assessed using magnetic resonance imaging and optimized voxel-based morphometry. Within the MDD group, further comparisons were performed focusing on the experience of maltreatment during childhood (23 MDD with child abuse vs 11 MDD without child abuse). Results Compared with healthy controls, the MDD patient group showed decreased GMD in the bilateral orbitofrontal cortices, right superior frontal gyrus, right posterior cingulate gyrus, bilateral middle occipital gyri, and left cuneus. In addition, the patient group showed increased GMD in bilateral postcentral gyri, parieto-occipital cortices, putamina, thalami, and hippocampi, and left cerebellar declive and tuber of vermis. Within the MDD patient group, the subgroup with abuse showed a tendency of decreased GMD in right orbitofrontal cortex, but showed increased GMD in the left postcentral gyrus compared to the subgroup without abuse. Conclusions Our findings suggest a complicated dysfunction of networks between cortical-subcortical circuits in MDD. In addition, increased GMD in postcentral gyrus and a possible reduction of GMD in the orbitofrontal cortex of MDD patients with abuse subgroup may be associated with abnormalities of body perception and emotional dysregulation.